The influence of variations in penetrating solar radiation on the diurnal and intraseasonal structure of the oceanic boundary layer - Van Roekel, Luke P., author; Randall, David A. (David Allan), 1948-, advisor; Ito, Takamitsu, committee member; Denning, A. Scott, committee member; Kirby, Michael, 1961-, committee member (Colorado State University. Libraries, 2010)
The upper portion of the ocean is fairly well mixed and turbulent. The turbulence within the ocean boundary layer (OBL) is regulated by many mechanisms. One process that is receiving a renewed interest is the effect of penetrating component of surface shortwave radiation on ocean dynamics. The influence of solar radiation has been parameterized in two ways. A limited set of models force all the incoming solar radiation to be absorbed in the top model layer. The second parameterization assumes that the irradiance (light) at a given level follows a multiple term exponential. Most commonly it is assumed that shortwave radiation is absorbed in two bands: visible and near infrared. The strength of the infrared absorption is assumed to be fixed. For the visible band, absorption depends on water clarity. Until recently, water clarity could take six different values (Jerlov water types). On climate scales, spatial and temporal variations in water clarity, based on surface chlorophyll, have a strong impact on the simulated ocean temperature, salinity, and momentum. For example, the sea surface temperature (SST) in the cold tongue is reduced. In addition, the strength of the Walker circulation is increased. However, this response is not consistent among different models and parameterizations. When chlorophyll is predicted, the influence of vertically variable water clarity on the thermodynamic and dynamic fields of the ocean can be examined. Studies that have incorporated an ecosystem model find minimal changes relative to using observed surface chlorophyll. Previous research has focused on longer climate time scales and most models do not consider vertical variations in water clarity. In this study the response of the ocean to diurnal and intraseasonal variations of water clarity is examined. The sensitivity to vertical variations in water clarity is also considered. To study the impact of variable solar radiation a model that accurately represents upper ocean physics is required. A new ocean mixing model is proposed that addresses some of the known deficiencies in previous models. The new model predicts entrainment based on turbulence at the OBL base, unlike other ocean models. An over prediction of the vertical heat flux in previous mixed layer models is avoided. The model framework discussed can be easily extended to any coordinate system. Further, this model can be coupled to an ocean biological model, which would determine the water clarity with depth, in a natural way. An evaluation of the new model against observations and a newly developed vector vorticity large eddy simulation (LES) model has shown that the new model preforms as well or better than previous OBL models in certain circumstances. This is especially with low vertical resolution. Since this version of the new model is local, it does not perform as well in pure convective simulations as OBL models with non-local forcing In this new model and K-Profile Parameterization (KPP), the temperature and velocity is very sensitive to variations in water clarity. Trapping more heat near the surface increases the temperature near the surface and confines daytime momentum input to a shallow layer. In addition, the depth of the thermocline is reduced as water clarity decreases. The simulated temperature and velocity fields are insensitive to subsurface variations in water clarity. The responses of the new model and KPP are similar when the turbidity of the column is taken as the near surface average. Two-dimensional simulations examining the influence of spatially variable turbidity lead to a slightly deeper thermocline and weaker near surface velocity relative to simulations with a zonally constant water clarity. It is found that models must allow solar radiation to penetrate beyond the top model level. Further, water clarity should be diagnosed from observed or predicted surface chlorophyll instead of the six Jerlov water types.
Keywords: chlorophyll; solar radiation; ocean; model; Solar radiation; Ocean-atmosphere interaction; Chlorophyll; Thermoclines (Oceanography)